Analisis Faktor yang Mempengaruhi Kesiapan Pembelajaran Praktik Klinik Pertama Mahasiswa STIKes Panti Rapih Prodi Diploma Tiga Keperawatan Yogyakarta - Bernadetta Eka Noviati; Dwi Antara Nugraha (I Care Jurnal Keperawatan STIKes Panti Rapih, 2020)
Background: Learning clinical practice in a hospital is one of the learning methods used to provide competent nurse assistance. Students who first underwent clinical learning has a level of preparedness that different from each other. Objective: This study aims to identify and analyze the factors that influence the readiness of School of Health Sciences Panti Rapih students to take part in learning the first practice of clinical nursing. Methods: The research was a quantitative analytic survey research using cross sectional approach. The population in the study were students of Nursing Diploma Study Program in School of Health Sciences Panti Rapih Yogyakarta. The sample in this study were all second semester students of Nursing Diploma Study Program at School of Health Sciences Panti Rapih Yogyakarta, who were still active and fulfilled the requirements to attend nursing clinical practice. The research instruments was prepared and developed by researchers and have been tested for validity and reliability with the results of all valid and reliable measuring tools. Results: The first physical readiness of students in learning clinical nursing practice was moderate readiness with 59 respondents (60.8%). Mental psychological readiness of students in attending the first clinical nursing practice learning that states ready as many as 54 respondents (55.7%). Material readiness of students in attending nursing clinical practice learning the first 97 respondents (100%) said they were ready. There is a correlation between physical preparation with mental-psychological readiness with low correlation with a Correlation Coefficient value of 0.273 and a significance value of p = 0.007. There is aminimum correlation between physical preparation and material readiness with a Correlation Coefficient of 0.137 and a significance value of p = 0.187. There is no correlation between mental psychological preparation with material readiness with a Correlation Coefficient value of 0.142 and a significance value of p = 0.16. There is a correlation between age and mental-psychological readiness with a low correlation level with a Correlation Coefficient of 0.302 and a significance value of p = 0.003. Conclusion: Research data on physical readiness, psychological mental readiness and material readiness show that more than 50% of respondents are ready. The results of the analysis show that the first factor influencing students in learning clinical nursing practice is age with a value of p = 0.003 then physical preparation with a value of p = 0.007. Keywords: readiness, clinical learning, students